Conserving the BLM’s Mandate: Will Conservation Leases Work? - Marlie Heiser (Washington University Journal of Law and Policy, 2026)
The Bureau of Land Management (BLM) has historically prioritized the management of productive ‘uses’ like oil, gas, mineral, and grazing leases on federal lands administered under the Federal Land Policy and Management Act (FLPMA). In an era where federal lands are positioned as a tool for climate change response, the BLM’s priorities have shifted toward conservation. In fact, the Biden administration Conservation and Land Health (CLH) Rule established a conservation leasing structure whereby private users can pay to conserve BLM lands. This interpretive shift renews a long-standing question: whether FLPMA—which speaks in terms of the ‘use’ of land—grants authority to lease for conservation. It further begs a practical question: can conservation efforts and productive ‘uses’ coexist? This Comment discusses the viability of interpreting conservation as a ‘use’ under the major questions doctrine and Loper Bright. In consideration of the history of BLM’s ‘use’-centric, commodity-focused approach and the practicality of leasing for conservation, this Comment posits that BLM’s shift in its interpretation of its leasing authority would not pass judicial scrutiny. And without proper incentives and mechanisms for lease renewals, the practical sustainability of conservation leasing is questionable. The BLM must re-center itself on FLPMA’s mandate for sustained yield and prohibition of unnecessary degradation of land. Under the statute, the BLM has always been a conservationist, and it cannot abdicate its duties by passing them to private lessees.
Keywords: #ConservationLeasing; #FLPMA; #PublicLandsPolicy; #MajorQuestionsDoctrine; #LoperBright; #ClimateResponsePublicLands; #UnnecessaryDegradation; #BidenAdministration; #FederalLandManagement; #PrivateConservationLeases